2017
DOI: 10.1111/gwao.12200
|View full text |Cite
|
Sign up to set email alerts
|

Doing gender in the ‘new office’

Abstract: This paper investigates how gender is performed in the context of an office setting designed to promote intensive, fluid networking. We draw on an ethnographically oriented study of the move of staff into a new office building constructed primarily from glass, and incorporating open plan offices, diverse collective areas and walking routes. Although the designers aimed to invoke changes in the behaviour of all staff, they conceptualized these changes in masculine terms. We therefore analyse the gender norms ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 33 publications
(77 reference statements)
0
33
0
Order By: Relevance
“…. at work mean to you?’), I followed Hirst and Schwabenland (2018) in the spirit of ‘ethnographic interviewing’ and allowed and encouraged interviewees to ‘shape the questions being asked and develop the focus of the research’ (p. 164). I also let participants decide where they’d like to be interviewed.…”
Section: Methodsmentioning
confidence: 99%
“…. at work mean to you?’), I followed Hirst and Schwabenland (2018) in the spirit of ‘ethnographic interviewing’ and allowed and encouraged interviewees to ‘shape the questions being asked and develop the focus of the research’ (p. 164). I also let participants decide where they’d like to be interviewed.…”
Section: Methodsmentioning
confidence: 99%
“…Vitti compares the shift of working through "natural" rhythms to tech giant Google's turn toward open office design, which involved a push for flexible workspaces over dedicated, individual offices (2020,195). Yet, an interview study released about two years before the publication of the book found that this approach to office reorganization leaves women feeling perpetually surveilled and newly scrutinized (Hirst and Schwabenland 2018). Vitti also points to Google as a model for parental leave (2020,196), though recent activism again defies this (Franceschi-Bicchierai 2019).…”
Section: Achieving Flomentioning
confidence: 99%
“…This transgressive sense of spatial productivity is taken up by Hirst and Schwabenland (2018) in a longitudinal ethnographic study of office space interaction. They emphasize how generative bodies are integral to sensemaking, and how personhood develops in a dialectic relation between space and body.…”
Section: Spatial Relations At Workmentioning
confidence: 99%